1981
DOI: 10.1007/bf02357028
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation studies of the leucocyte inhibitor of urokinase by cathepsin D

Abstract: Leucocytes contain an urokinase inhibitor, that can be inactivated by cathepsin D. In this work biochemical and immunological studies on the inactivation of this inhibitor by cathepsin D are presented. Examinations by polyacrylamide gel electrophoresis and SDS electrophoresis indicate that cathepsin D inactivates urokinase inhibitor by hydrolysis of the inhibitor molecule and that the degradation needed for total inactivation is different from that for formation of the precipitin line with antibodies. The conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1983
1983

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…It was already known that these protein isoinhibitors inhibit intracellular proteinases of cysteine and serine type. We had also found that cathepsin D does not inactivate (degrade) sericystatin, whereas it does inactivate other types of intracellular inhibitors, such as the inhibitors of urokinase [17,18] and elastase [17].…”
Section: Discussion Referencesmentioning
confidence: 95%
“…It was already known that these protein isoinhibitors inhibit intracellular proteinases of cysteine and serine type. We had also found that cathepsin D does not inactivate (degrade) sericystatin, whereas it does inactivate other types of intracellular inhibitors, such as the inhibitors of urokinase [17,18] and elastase [17].…”
Section: Discussion Referencesmentioning
confidence: 95%